2017
DOI: 10.1002/2017jd027252
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of SST Patterns on Rapid Intensification of Typhoon Megi (2010)

Abstract: Typhoon Megi (2010), a very intense tropical cyclone with a minimum central pressure of 885 hPa, was characterized by especially rapid intensification. We investigated this intensification process by a simulation experiment using a high‐resolution (0.02° × 0.02°) three‐dimensional atmosphere‐ocean coupled regional model. We also performed a sensitivity experiment with a time‐fixed sea surface temperature (SST). The coupled model successfully simulated the minimum central pressure of Typhoon Megi, whereas the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 62 publications
(94 reference statements)
1
23
0
Order By: Relevance
“…The major cooling, peaking at approximately −1.7 • C, appears to the rhs of the track from around 117.0 • E longitude to the edge of continental shelf and is roughly parallel to the shelf break. Such right-hand-side cooling is usually associated with a strong and fast-moving typhoon, as was suggested in earlier studies [8,27,36]. SST over the shallow continental shelf barely cooled, which is also similar to the observations.…”
Section: Typhoon Hato With Sst Distributionssupporting
confidence: 89%
See 1 more Smart Citation
“…The major cooling, peaking at approximately −1.7 • C, appears to the rhs of the track from around 117.0 • E longitude to the edge of continental shelf and is roughly parallel to the shelf break. Such right-hand-side cooling is usually associated with a strong and fast-moving typhoon, as was suggested in earlier studies [8,27,36]. SST over the shallow continental shelf barely cooled, which is also similar to the observations.…”
Section: Typhoon Hato With Sst Distributionssupporting
confidence: 89%
“…According to the sensitive experiments that conducted by Halliwell et al [26], small TCs with fast translation speed tend to be less sensitive to the SST changes, owing to the small eyewall coverage of the specific water and insufficient response time. However, Kanada et al [27] suggested that even weak local SST responses could affect the inner-core structure and intensity evolution in TCs by altering the CAPE and moisture distributions. SST distributions also impact the intensification rate of TCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nasuno et al (2016) showed that small latent heating differences over the ocean can delay the development of TCs. Kanada et al (2017b) indicated that sea surface cooling can suppress the delayed evolution of the simulated TCs. However, it is not the main scope of this study to improve the boundary condition (SSTs) and surface physics schemes.…”
Section: Resultsmentioning
confidence: 97%
“…Although the time profile of the simulated central pressure appears to be delayed for approximately 1 day compared with that of the best track data, the simulated profile reasonably captures the decreasing slope and minimum central pressure of the best track data. Several studies have shown delayed intensification of simulated TCs (Oku et al 2010;Takayabu et al 2015;Nasuno et al 2016;Kanada et al 2017b;Nayak and Takemi 2019). Takayabu et al (2015) indicated the effect of initial and boundary conditions on TC simulations.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established by previous studies that warmer SSTs are correlated with TCs that undergo RI. Although Kanada et al (2017) suggested that the RI is sensitive to the SST pattern, the SST at the storm center is used here as a basic and more independent (of storm size) diagnostic. Figure 5 shows time series of SST and the value of 200 -850-hPa vertical wind shear at the storm center following with the storm movement along the forecast time.…”
Section: Rapid Intensificationmentioning
confidence: 99%